Análise acústica dos sons da deglutição em pacientes traqueostomizados acometidos por traumatismo cranioencefálico. - Lemos , Raquel Guidotti (2016)
INTRODUCTION: The instrumental evaluation combined with the clinical swallowing exam contributes in a decisive way when defining the succeeding practices. Mechanisms that enable these practices call for new tested and explored methodologies. OBJECTIVE: To determine the viability of use of the acoustic analyzes of the swallowing sounds as a conjugated method to the clinical evaluation in a tracheostomized patient, affected by traumatic brain injury (TBI). METHODOLOGY: Ten adult patients around 43,6 years old, 8 males and 2 females, hospitalized in the Intensive Care Unit at the Hospital do Trabalhador in Curitiba-PR from May to July in 2016 participated in this study. They were affected by TBI, confirmed by Computed Axial Tomography (CAT), went through a tracheotomy and were using enteral nutrition only. The Tracheal Decannulation Protocol (TDP) was applied for the clinical evaluation and the Doppler Sonar was used for the cervical auscultation. RESULTS: All patients presented a Glasgow level over 11; 60% with metallic cannula, 100% maintained the breathing standard, effective cough and oratracheal secretion occurrence, most in a light and fluid color. According to the acoustic deglutination analyzes of the pasty consistence the peak frequency was in average 665,50 Hz, the intensity 63,60 dB, the waving time 1,59 s, and the timing between the deglutinations 5,45 s. To the liquid consistence, 719,60 Hz, 75,40 dB, 1,37 s, and 5,23 s respectively. The presence of acoustic signal of laryngeal elevation, noise between deglutination, acoustic suggestive signal of residue in laryngeal recess were observed in 50% of the patients, in both pasty and liquid dietary consistence. CONCLUSION: The study suggested that the Doppler Sonar may be used as a conjugated method for a clinical evaluation of the dysphasia to the decannulation in patients affected by traumatic brain injury.